Proektirovanie tennisnych pokrytij i adaptacija sportsmena k uslovijam igry na nych - Portnova, O. Ju. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The tennis player has to play on a platform with various coverings. There are four versions of a covering of tennis courts. The character of a covering renders the big influence on speed and height of rebound of a ball and accordingly on style and efficiency of game, and also on a traumatism of players. The manufacture of an artificial lawn for tennis is described for the first time.